Influence of Exposing Root Canal Dentin to Calcium Hydroxide on Its Flexural Strength - Diatri Nari Ratih (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2011)
Calcium hydroxide has been used extensively in endodontic treatments, for instance as an intra-canal dressing; however, the exposure of root canal dentin to calcium hydroxide may affect its flexural strength and could have important clinical implications for endodontic treatment. The purpose of this in vitro study was to investigate the influence of calcium hydroxide on the flexural strength of root canal dentin.Seventy-two extracted single-rooted human mandibular premolars were used in this study. Each tooth was instrumented using crown-down technique and was irrigated using sterile saline. The teeth were assigned into three groups of 24 each. The prepared root canal system of each tooth was filled with calcium hydroxide mixed with sterile saline (group 1), a calcium hydroxide commercially available product (UltraCal®) (group 2) or saline solution (group 3, as control). The apices and access opening were sealed using composite resin, and the teeth were immersed in artificial saliva. After 7, 14 and 30 days of immersion, the inner root canal dentin of 8 teeth respectively from each group were sectioned to create dentin bars (1 X 1 mm, with 7 mm in length). Each dentin bar then was subjected to a three-point bending flexural test using MTS (Universal Testing Machine). Data gathered were then analyzed using two-way ANOVA, followed by Tukey’s test with the level of significance of 95%. The results showed that exposure to calcium hydroxide either using calcium hydroxide mixed with sterile saline or UltraCal® for 14 and 30 days can reduce flexural strength of root canal dentin compared to control group (p<0.05). In contrast, after 7 days exposure, there was no significantly different of flexural strength between three groups (p>0.05). It can be concluded that calcium hydroxide reduced the flexural strength of root canal dentin. The longer the exposure to calcium hydroxide would produce a greater effect on flexural strength of root canal dentin.